Spontaneous Bilateral Tubal Ectopic Pregnancy: A Case Report and a Comprehensive Review - Bhusal, Amrit; Yogi, Tek Nath; Rai, Prashant; Katwal, Shailendra; Mahat, Asim; Agrawal, Ajay (Journal of BP Koirala Institute of Health Sciences, 2024)
An ectopic pregnancy occurs when a fertilized ovum implants outside the uterine cavity. It has an estimated incidence of 1-2% and is the most common surgical emergency in women of reproductive age. Fallopian tubes are the most common site for ectopic pregnancy. The incidence of ectopic pregnancy has been increasing in recent years because of the increasing use of Assisted Reproductive Technology, use of Intrauterine Devices, Pelvic Inflammatory Disease, and a history of previous ectopic pregnancy or tubal surgery. Bilateral tubal pregnancies following natural conception account for the rarest form of ectopic pregnancy. We report a case of a 27-years old primigravida with spontaneous bilateral tubal ectopic pregnancy managed successfully without any complications. Bilateral tubal ectopic pregnancy should be suspected in patients presenting with the clinical triad of amenorrhea, abdominal pain and vaginal bleeding, despite its rarity in spontaneous conception.